2011
DOI: 10.1021/bm101482r
|View full text |Cite
|
Sign up to set email alerts
|

Surface Charge Affects Cellular Uptake and Intracellular Trafficking of Chitosan-Based Nanoparticles

Abstract: Chitosan-based nanoparticles (NPs) are widely used in drug delivery, device-based therapy, tissue engineering, and medical imaging. In this aspect, a clear understanding of how physicochemical properties of these NPs affect the cytological response is in high demand. The objective of this study is to evaluate the effect of surface charge on cellular uptake profiles (rate and amount) and intracellular trafficking. We fabricate three kinds of NPs (∼ 215 nm) with different surface charge via SPG membrane emulsifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
339
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(354 citation statements)
references
References 32 publications
14
339
0
1
Order By: Relevance
“…These results indicate that CS:pDNA has high importance for the efficacy of transfection. This is relevant with previously reported data about dependence of the surface charge ratio on the efficacy of polyplex-based gene delivery (Erbacher et al, 1998b;Lavertu et al, 2006;Romoren et al, 2003;Yue et al, 2011). Furthermore, independently from CS:pDNA Fig.…”
Section: Cell Type-dependent Cytostatic Effect Of Cns and Cns-pdnasupporting
confidence: 81%
“…These results indicate that CS:pDNA has high importance for the efficacy of transfection. This is relevant with previously reported data about dependence of the surface charge ratio on the efficacy of polyplex-based gene delivery (Erbacher et al, 1998b;Lavertu et al, 2006;Romoren et al, 2003;Yue et al, 2011). Furthermore, independently from CS:pDNA Fig.…”
Section: Cell Type-dependent Cytostatic Effect Of Cns and Cns-pdnasupporting
confidence: 81%
“…Similarly, it is commonly accepted in the literature that positively charged nanoparticles are more uptaken than other kinds of nanoparticles (Chung et al 2007;Yue et al 2011). For instance Guarnieri et al reported that (25 to 115 nm) particles surface functionalized with positively charged groups were more uptaken than those functionalized with negatively charged groups (Guarnieri et al 2014).…”
Section: Discussionmentioning
confidence: 90%
“…Since the charge is described as important parameter to influence the interaction with cell membrane and govern the cellular uptake [3,40,41] DPPC mixed with DPPG was also used to represent the charged membrane model in the penetration experiments. The interaction of NPs with lipid layers was studied in Langmuir-balance experiments, where the adsorption and/or penetration of the particles into the lipid layer is the indication of their membrane affinity.…”
Section: Membrane Affinitymentioning
confidence: 99%